ICT Practitioners’ Perception of Working from Home During the Covid-19 Pandemic: Exploring Gender Differences - Canedo, Edna Dias; Calazans, Angelica; Silva, Geovana; Masson, Eloisa (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2022: Anais do XXXVI Simpósio Brasileiro de Engenharia de Software, 2022)
The Covid-19 pandemic has impacted various aspects of society’s coexistence, especially in relationships and work routines. Working from home (WFH) was one of the measures adopted by companies in this period, especially for software development. In this context, professionals had to conciliate their domestic and work routines, and this can make gender differences more evident. This work aims to investigate the impact of working from home (WFH) on ICT practitioners’ personal and professional lives during the pandemic period considering gender differences. We carried out a literature review and a survey to collect the perceptions of ICT practitioners regarding the WFH during the Covid-19 pandemic period, besides the challenges they faced, considering aspects related to gender differences. Our findings reveal that the majority of Chief information officers (CIOs) are men, and only 30.37% of women occupy leadership positions in the projects in which they participate, indicating that women are still underrepresented in leadership positions. Concerning productivity, participants claimed that they were more productive during the pandemic. In summary, this work can help software development teams understand the effects of Covid-19 on development practices and create policies to increase team engagement. Moreover, it gives prominence to related topics such as the long-term impact of the pandemic on work routines.